Larry Smith and world Englishes - Bolton, Kingsley (2020)
This article discusses the contribution of Professor Larry E. Smith to the field of world Englishes (WE), a linguistic and educational enterprise in which Professor Smith was a founding figure. The article traces the development of Smith's thinking on world Englishes from early attempts to theorize English as an ‘international auxiliary language’ (EIAL), to a full theorization of world Englishes as a dynamic new field of study in the 1980s and 1990s. This discussion of Larry Smith's work also acknowledges his contribution to such other related areas of study as intercultural communication, and intelligibility studies, as well as his enduring contribution to the World Englishes journal, and the International Association for World Englishes (IAWE).